2009
DOI: 10.1002/hc.20536
|View full text |Cite
|
Sign up to set email alerts
|

A novel stereoselective synthesis of (Z)‐α‐arylsulfanyl‐α,β‐unsaturated ketones via Stille coupling of (E)‐α‐arylsulfanylvinylstannanes with acyl halides

Abstract: (E)-α-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Some ( Z )‐α‐SAr‐chalcones were synthesized through the Stille coupling of ( E )‐α‐arylsulfanylvinylstannanes with acyl halides in the presence of Pd(PPh 3 ) 4 catalyst and CuI cocatalyst as shown in Figure 39 [155] . Later, the same ( Z )‐α‐SAr‐chalcones were prepared by a one‐pot reaction that involved palladium catalyzed hydrostannylation of acetylenic sulfides with tribytylin hydride (Bu 3 SnH) followed by Stille coupling with acyl chloride [156] …”
Section: Different α‐Substituted Chalconesmentioning
confidence: 99%
“…Some ( Z )‐α‐SAr‐chalcones were synthesized through the Stille coupling of ( E )‐α‐arylsulfanylvinylstannanes with acyl halides in the presence of Pd(PPh 3 ) 4 catalyst and CuI cocatalyst as shown in Figure 39 [155] . Later, the same ( Z )‐α‐SAr‐chalcones were prepared by a one‐pot reaction that involved palladium catalyzed hydrostannylation of acetylenic sulfides with tribytylin hydride (Bu 3 SnH) followed by Stille coupling with acyl chloride [156] …”
Section: Different α‐Substituted Chalconesmentioning
confidence: 99%
“…However, the Stille coupling reaction of the intermediates 2 with aliphatic acyl chlorides did not occur under the same conditions perhaps due to the presence of the steric barrier from α-aryl groups. It was reported that the Stille coupling reactions of sterically hindered (E)-α-selanyl-vinylstannanes, 20 (E)-α-arylsulfonylvinylstannanes 21 and (E)-α-arylthiovinylstannanes 22 with aliphatic acyl chlorides was also unsuccessful.…”
mentioning
confidence: 99%